Traceable Radiometry Underpinning Terrestrial- and Helio-Studies (TRUTHS): An Element of a Space-Based Climate and Calibration Observatory - Fox, Nigel; Green, Paul (Remote sensing (Basel, Switzerland), 2020)
The Earth’s climate is undoubtedly changing; however, the time scale, consequences, and causal attribution remain the subject of significant debate and uncertainty. Detection of subtle indicators from a background of natural variability requires measurements over a time-base of decades. This places severe demands on the instrumentation used, requiring measurements of sufficient accuracy and sensitivity that can allow reliable judgements to be made decades apart. The International System of Units (SI) was developed to address such requirements, providing a reference framework tied to invariant constants of nature. However, ensuring and maintaining SI traceability of sufficient accuracy in instruments orbiting the Earth presents a significant new challenge to the Earth Observation and metrology communities. This paper describes a new satellite mission, called Traceable Radiometry Underpinning Terrestrial- and Helio- Studies (TRUTHS), which enables, for the first time, high-accuracy SI traceability to be established in orbit. The direct use of a ‘primary standard’ and replication of the terrestrial traceability chain extends the SI into space, in effect realizing a ‘metrology laboratory in space’ providing and enabling SI-traceable measurements of unequivocal accuracy in the solar reflective domain—an enabling element of an international space-based climate observing system. TRUTHS will not only provide a benchmark of the radiation state of the planet (incoming and outgoing) from which to compare change in the shortest time possible, but also facilitate an upgrade in performance of the Earth Observing system as a whole, through ‘in-orbit’ reference calibration.